The Issue of Language in Children Books - Özkan, Nazmiye; Yılmaz, Bülent (Information World, 2001)
This study investigates how illustrated Turkish children’s books, tales. stories and novels that are prepared tor the age group of 7-14 years has changed from the point of language rules between 1967 and 1997. We examined a total of 71 children’s books, 24 of which were published in 1967 and 47 in 1997, on the basis of the following criteria. syntax, spelling and type-setting errors, use of punctuation marks, foreign and slang words. We found that the use of language in Turkish children’s books has improved positively between 1967 and 1997.